Bangladesh, economic and social challenges of globalisation - Muqtada, M.; Singh, Andréa Menefee, 1943-; Rashid, M. Ali (Mohammed Ali); International Labour Organisation (Dhaka : University Press, 2002)
Contributed papers presented at a national tripartite workshop.
"A study prepared for the International Labour Office, Geneva."
Includes bibliographical references (p. [225]-232) and index.
Keywords: Globalization -- Economic aspects -- Bangladesh -- Congresses; Globalization -- Social aspects -- Bangladesh -- Congresses; Bangladesh -- Economic policy -- Congresses; Bangladesh -- Social policy -- Congresses